THE PERSPECTIVE OF THE TENTH GRADE STUDENTS OF MUHAMMADIYAH VOCATIONAL HIGH SCHOOL 2 OF PALEMBANG TOWARDS LEARNING WRITING DESCRIPTIVE TEXTS THROUGH CONTENT-BASED INSTRUCTION (CBI) - Ammarullah Muhammad; Mulyadi Mulyadi; Hermansyah Hermansyah (Esteem Journal of English Education Study Programme, 2020)
The problem of this study was â€œHow are students perspective of writing descriptive text through content-based instruction (CBI)?â€. Therefore, the objective of this study was to know the perspective of the students learning writing descriptive texts through content-based instruction. This study applied qualitative method. The population of this study was the tenth grade students of accountant 1 class in the academic year of 2019/2020 with the total of 30 students taken by using purposive sampling. The data were collected by using questionnaire, and were analyzed into interpretation. Based on the interpretation of students perspective of content-based instruction, the students said that content-based instruction could Â help them to improve their ability to write descriptive text.Keywords: Perspective, Writing, Descriptive Texts, and Content-Based Instruction.